Analysis of Free Fatty Acid in Frying Oils of Various Foodstuffs - Setianingsih, A.; Febrianto, F.; Riyani, A. (Indonesian Journal of Chemistry and Environment, 2018)
Cooking oil is one of the basic human needs as food processing media. Repeated use of cooking oil by heating at high temperature will produce free fatty acid levels. This study aims to determine the levels of free fatty acids in frying oils of various foodstuffs that is chicken, catfish, and flour with acid base titration method.Â  The study population was frying oils of various foodstuffs of 0, up to 5th. The results of fatty acid levels in the repeated use of chiken (sampel A), catfish (sample B) and flour foodstuffs shows the Fatty Acid levels exceed safe limits set by SNI 7709:2012. The oil before was used = 0.24% and on sample A: the oil of first frying (A1) = 0.49%,Â  5th frying (A5) = 0.73%. ALB sample B: first frying (B1) = 0.49%, 5th frying (B5) = 0.68%. ALB sample C: first frying (C1) = 0.49%, 5th frying (B5) = 0.77%. The increase of free fatty acid was influeced of the oil was many used to frying because level water in foodstuffs.